SISTEM DIAGNOSIS JERAWAT MENGGUNAKAN METODE FORWARD CHAINING EXPERT SISTEM BERBASIS WEB - Nurani Hidayat; Husni Sulaiman; Andi Nurul Faizah (Institut Teknologi dan Bisnis Bina Adinata, 2024)
The goals of this study are as follows: (1) to learn about the acne diagnosis system using the web-based forward chaining expert system method; (2) Implementing an acne diagnosis system using a web-based, forward-chaining expert system method. This study applies the